Bea Perolehan Hak Atas Tanah Dan Bangunan (Bphtb) Atas Warisan, Apakah Warisan (Dalam Garis Keturunan Sedarah) Harus Dikenai BPHTB? - Silalahi, Eka Wijaya (UI Scholars Hub, 2019)
Tax is the main element of income for the state treasury so that the tax function is essential in financing all needs in the administration of the state. This study examines and explores whether inheritance can be taxed, especially BPHTB, for inheritance in the form of land or buildings. This study uses a normative juridical method (Library Research) with secondary data as the source. The results of the study indicate that the inheritance (in blood lineage) in the form of land or buildings should not be taxed (Customs and Land Rights Acquisition Fees).